2003
DOI: 10.1034/j.1600-0781.2003.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Phototesting with a divergent UVB beam in the investigation of anti‐inflammatory effects of topically applied substances

Abstract: The divergent beam protocol can be used to demonstrate and quantify the effects of topical agents on the UVB reaction, in terms of reaction diameter, mean perfusion and changes in dose-response characteristics. The dose-response approach seems to be applicable even in diagnostic testing of an individual patient's response to UVB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This resulted in an illuminated skin area with a diameter of 4.5 cm. Figure 1 shows the relationship between dose, LDPI‐response and visual diameter assessment as developed in reference (12).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This resulted in an illuminated skin area with a diameter of 4.5 cm. Figure 1 shows the relationship between dose, LDPI‐response and visual diameter assessment as developed in reference (12).…”
Section: Methodsmentioning
confidence: 99%
“…LDPI enables a quantitative estimation of the tissue blood perfusion, by scanning a laser beam over the skin area of interest. The measurement results in a two‐dimensional data set representing the spatial variations of the skin blood perfusion (10–12, 16, 17). The instrumental settings used for this study were a scanner‐head to skin distance of 9 cm, 40 × 40 measurement sites, low resolution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also showed that topical corticosteroids (betamethasone-17-valerate and betamethasone-17, 21-dipropionate), diphenhydramine hydrochloride, and indomethacin reduced UVB erythema when they were applied after irradiation. Falk et al (15) also showed that application of the topical steroid clobetasol diproprionate after UVB provocation decreased the inflammatory response. In our study, we applied topical steroid clobetasol-17-propionate cream and ointment immediately before UVB instead and showed blocking effects.…”
Section: Discussionmentioning
confidence: 97%